SOSIALISASI ENTREPRENEUR MINDSET BAGI MAHASISWA UNTUK MENINGKATKAN MINAT BERWIRAUSAHA - Nurul Ittaqullah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The development of digital technology and increasingly competitive job market challenges require university students to possess not only academic competence but also entrepreneurial skills and adaptive mindsets. However, many students still tend to orient themselves as job seekers rather than job creators. This community service activity aims to provide socialization regarding entrepreneur mindset to improve students’ understanding, motivation, and entrepreneurial interest in the digital era. The activity was conducted through educational seminars, interactive discussions, motivational sessions, and sharing experiences related to digital business opportunities. The method used in this activity was descriptive qualitative with a participatory approach. Data collection techniques included observation, documentation, and participant responses during the activity. The results showed that the socialization activity positively impacted students’ understanding of entrepreneurial concepts, entrepreneurial motivation, self-confidence, and awareness of digital business opportunities. Students also demonstrated higher enthusiasm in developing creative business ideas based on technology and social media. Therefore, this activity is expected to become an initial step in shaping entrepreneurial mindsets among students and encouraging the emergence of young entrepreneurs within higher education environments.